The Effectiveness of the M.U.R.D.E.R Strategy to Solve Problems in Learning Skills of Top and Bottom Facing Service for Student in the Volleyball - Saeed Gheni Noori (Journal of Global Pharma Technology, 2016)
The study aimed at identifying the efficacy of the murder strategy to solve problems in learning the top-down and bottom-up service skills of volleyball, and researchers have identified the research community of fifth graders, the bio branch of the Rafidain preparatory boys' school in Baghdad governorate for the 2017-2018 school year, the number (86) students, 36 students were selected as a random search sample, divided into two female and experimental groups of 15 students per group and the rest of the students selected for the exploratory experiment, the experimental group exercised a murder strategy to solve the problems, while the officer group exercised the traditional method, the program was applied by two educational units per week for 6 weeks, and in light of the findings of the two researchers, they concluded that the murder strategy to solve the problems had a positive impact on the speed of learning the artistic performance and the accuracy of the service skills facing The top and bottom of the trial group, and the use of this strategy for this group was more influential than in the security group method of learning the performance of the top-down and bottom-facing service skills.Keywords: M.U.R.D.E.R strategy, Top and bottom facing service.